Following The Rough Guide to Góra Kalwaria: Constructing Memory Tourism of Absence in Post-Communist Poland. (3rd July 2018) - Cole, Tim
Abstract : This article uses comparative analysis of the editions of The Rough Guide to Poland published in the 1990s to argue that a memory tourism of absence was being offered to western visitors. This differed from existing categories of tourism — dark tourism, Holocaust tourism, Jewish heritage tourism — by directing visitors to see the places where Jews lived before the Holocaust, and where their memory was in danger of being erased in both the communist and post-communist era. In this context, western visitors were not only directed to sites to witness absence, but also to engage in acts of memory tourism that were charged with a sense of moral purpose. A concern with absence was more widely shared in the decade following the fall of the Berlin Wall, and this memory tourism of absence is one that — like all acts of tourism — can and needs to be historicized.